The transformative potential of textbooks: Food waste knowledge and pedagogical text styles in Finnish Home Economics, Geography, and Biology textbooks - Pollari, Milja; Autio, Minna; Elorinne, Anna-Liisa (Nordic Journal of Comparative and International Education (NJCIE), 2024)
Education is recognized as crucial in addressing unsustainable practices, such as food waste. One of the aims of interdisciplinary food education in basic education is to promote sustainable food waste behavior, which can be promoted by transformative learning. This study examined how food waste is addressed in nine Finnish basic education textbooks. The content related to food waste and the pedagogical style of the texts were analyzed from home economics, biology, and geography textbooks designed for secondary level education (grades 7–9, age 13–16). The results were analysed to assess their potential to promote transformative learning. All of the textbooks approached the topic of food waste from the perspective of their own subject, and none presented it as an interdisciplinary phenomenon. Home economics textbooks focused on students' perspectives, emphasizing food waste reduction and waste sorting. Geography textbooks frequently explored the topic in the context of the food supply chain or at a global level, while biology textbooks primarily addressed the sorting of food waste. The textbooks primarily used a neutral text style focusing on information transmission. In some contexts, a persuasive style was employed to encourage critical thinking and action. The participative style, which encourages active student engagement, was utilized the least in all textbooks, and primarily for exercises. By integrating learning-supportive text styles (such as participative and persuasive), including student tasks related to food waste, and fostering an interdisciplinary understanding of food waste, textbooks have the potential to transform student learning and engagement in sustainable food practices.